AQUAHUB impact evaluation: Final assignment report - Arnold Groh; Margarita Langthaler; Werner Siebel; Stefan Wolf; Oskar Kabbeck; Sofia Hohenauer (Austrian Foundation for Development Research (ÖFSE), 2024)
ÖFSE was commissioned by the BOKU to undertake an impact assessment of the "Education and Research Hub for the Sustainable Management of Aquatic Ecosystems in Eastern Africa (AQUAHUB)" project. The assessment was supposed to cover the whole project period from 1975 to 2021, when AQUAHUB was known as "International Post-Graduate Training Programmes in Limnology (IPGL)". The AQUAHUB project serves two main purposes: supporting natural resource preservation and fostering Higher Education Science and Technology (HEST) systems in the Eastern African region. AQUAHUB intends to strengthen individual and institutional research capacities to allow for long-term independent and context-relevant knowledge production in the region. The purpose of the impact assessment is to support the further development of the AQUAHUB project through the promotion of organisational learning and support to decision making at the strategic and the operational level. The assessment aims at enhancing the understanding of change processes induced by the project over time and the project's impact mechanisms, in particular in relation to the given societal context. The project team has mainly used qualitative methods (alumni workshops, interviews), complemented by quantitative tools (alumni survey, publication analysis). The assessment has included extensive data collection phases in Vienna, Kenya, Uganda and Ethiopia.
Keywords: 330